Anterior Septal Reconstruction for Treatment of Severe Caudal Septal Deviation: Clinical Severity and Outcomes. (16th April 2015) - Surowitz, Josh; Lee, Matthew K.; Most, Sam P.
Abstract : Objective: To report the long‐term efficacy of a modified extracorporeal septoplasty technique in the treatment of anterocaudal septal deviations. Study Design: Case series with chart review. Setting: Academic tertiary care medical center. Subjects and Methods: Data were obtained by a retrospective review of patients treated by a single surgeon (S.P.M.) from December 2010 to April 2014. A total of 77 patients (52 male, 25 female) met inclusion criteria. The Nasal Obstruction Septoplasty Effectiveness (NOSE) scale and a visual analog scale (VAS) were administered to all patients preoperatively and at each postoperative visit. Statistical analysis was performed using a matched‐pair t test comparing preoperative and postoperative NOSE and VAS scores. A recently described severity scale for nasal obstruction was applied to NOSE scores to demonstrate postoperative results. Results: Average follow‐up was 4.7 months. Average preoperative NOSE and VAS scores were 68.2 ± 17.4 and 7.2 ± 1.8, respectively, placing these patients in the "severe" symptoms classification. Average NOSE and VAS scores in the early postoperative period (1‐3 months after surgery) were 21.1 ± 19.8 ( P <. 0001) and 2.1 ± 2.6 ( P <. 0001), respectively. Average NOSE and VAS scores in the late postoperative period (>3 months after surgery) were 15.8 ± 19.0 ( P <. 0001) and 1.4 ± 1.8 ( P <. 0001), respectively. Both early and late postoperative NOSE scores represented "mild" symptomatology. Conclusions: Anterior septal reconstruction represents a powerful method for correction of nasal valve stenosis resulting from severe anterocaudal septal deviations.